PENGEMBANGAN BAHAN AJAR BANGUN RUANG SISI DATAR MENGGUNAKAN STRATEGI THINKING MAPS - Gusni Satriawati; Gelar Dwirahayu; Yu’thika Mardiyah (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2021)
This study aims to develop teaching materials using a thinking maps strategy on the flat side space building material. Thinking Maps is a learning strategy with eight visual maps, where each map has an essential thinking ability. This research uses the Thinking Maps type: double bubble map, treemap, and multi-flow map. The selection of trial subjects used the purposive sampling technique in class VIII SMP/MTs students. The method used in this research is development research with a 4-D model from (Define, Design, Develop, and Disseminate). The results showed that the teaching materials developed had perfect criteria based on content feasibility, language feasibility, presentation feasibility, teaching material design, thinking maps strategy, and evaluation of teaching materials. The student responses based on the quality aspects of the presentation of the material, the creation of teaching materials, and the benefits have perfect criteria. Thus, this teaching material is included in the ideal measures and can use in learning mathematics for class VIII.